2009
DOI: 10.1007/s11214-009-9490-0
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Theory and Simulations of Large-Scale Dynamos

Abstract: Recent analytical and computational advances in the theory of large-scale dynamos are reviewed. The importance of the magnetic helicity constraint is apparent even without invoking mean-field theory. The tau approximation yields expressions that show how the magnetic helicity gets incorporated into mean-field theory. The test-field method allows an accurate numerical determination of turbulent transport coefficients in linear and nonlinear regimes. Finally, some critical views on the solar dynamo are being off… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 106 publications
0
36
0
Order By: Relevance
“…In the context of solar cycle models, one could also expect the Lorentz force to reduce the amplitude of differential rotation until the effective dynamo number falls back to its critical value, at which point the dynamo again saturates 11 . The third class of quenching mechanism listed above has not yet been investigated in detail, but numerical simulations of MHD turbulence indicate that the effects of the small-scale turbulent magnetic field on the -effect can be profound (see Pouquet et al, 1976;Durney et al, 1993;Brandenburg, 2009;Cattaneo and Hughes, 2009).…”
Section: Backreaction On Large-scale Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of solar cycle models, one could also expect the Lorentz force to reduce the amplitude of differential rotation until the effective dynamo number falls back to its critical value, at which point the dynamo again saturates 11 . The third class of quenching mechanism listed above has not yet been investigated in detail, but numerical simulations of MHD turbulence indicate that the effects of the small-scale turbulent magnetic field on the -effect can be profound (see Pouquet et al, 1976;Durney et al, 1993;Brandenburg, 2009;Cattaneo and Hughes, 2009).…”
Section: Backreaction On Large-scale Flowsmentioning
confidence: 99%
“…The issue hinges on helicity conservation and flux through boundaries, and subtleties of flow-field interaction in MHD turbulence. For recent entry points into this very active area of current research, see , Blackman and Field (2000), Dobler (2001), andBrandenburg (2009).…”
Section: What Limits the Amplitude Of The Solar Magnetic Field?mentioning
confidence: 99%
“…Results exhibited a self-similar inverse cascade of magnetic helicity from small to large scales, 5 which was later demonstrated in idealized numerical simulations of MHD turbulence [60,61]. However, MHD convection simulations have demonstrated that rotation alone is not sufficient to promote the generation of large-scale fields by means of an inverse cascade of magnetic helicity; rather, results are sensitive to boundary conditions, geometry and the strength and orientation of rotational shear (reviewed by Tobias et al [62] and Brandenburg [63]). …”
Section: (B) Large-scale Dynamos: From Fluctuations To Fluxmentioning
confidence: 97%
“…One way to introduce some non-linearity is to implement the so-called α-quenching, which is supposed to represent the feedback of the magnetic field on the small-scale motions that are responsible for the α-effect, but it is not clear how that quenching should be implemented (see Brandenburg 2009). …”
Section: Mean Field Dynamomentioning
confidence: 99%